DESCRIPTION OF THERMOPHILIC BACTERIA WITH KERATINASE ACTIVITY FROM TWO HOT SPRINGS IN ALMATY REGION (Experimental biology, 2025)
Keratin is an insoluble protein resistant to the degradation by many proteolytic enzymes. Among all poultrywaste, feathers and down are of particular interest, as they contain about 65% feed protein (specialized protein—keratin). Biotechnological methods are considered economical and environmentally friendly, making microbialkeratinolytic hydrolysis an optimal alternative for enhancing the nutritional value of feather waste. This study providesgeneral information about keratinases produced by microorganisms with keratinolytic activity. Keratinolytic bacteria were isolated from eight isolates obtained from the hot springs of Kerimagas and Nurly-Arasan, located in the Almaty region of Kazakhstan. Two isolates (Kh5 and Nh2) showing relatively high activity were selected, and their crude keratinase activity was partially characterized. The Kh5 isolate demonstrated the highest keratinolytic activity. In the study of crude keratinase under various pH and temperature conditions, it was observed that the Kh5 isolate was most active at pH 5.5, while the Nh2 ...
Keywords: feathers, keratinase, keratinolytic activity, hot springs.